2016
DOI: 10.4038/josuk.v10i0.7991
|View full text |Cite
|
Sign up to set email alerts
|

An Exact Solution of Non-Newtonian Peristaltic Flow in a Tube : Rabinowitsch Fluid Model

Abstract: With the development of medical science, non-Newtonian fluids have taken on added significance with a variety of applications in real life. The flow of non-Newtonian fluids in tubes and pipes plays a vital role in daily life. The examples of such applications are medical instruments, human body, machines, etc. The study of such mechanisms with the Newtonian fluids has not been found satisfactory due to nonlinear behavior of stress strain relationship. In the present analysis, the study of peristaltic flow in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…Shapiro et al [5] and Fung and Yih [7] scrutinized the peristaltic flows with some hypotheses, such as long wavelength approximation, low Reynolds number, and small amplitude ratio. e problem of peristaltic flow in a tube of Rabinowitsch fluid was scrutinized by Singh and Singh [8]. Singh [9] examined the exact solution of Rabinowitsch peristaltic flow in a tube, and found that the pseudoplastic and dilatant fluids counted on the instantaneous flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Shapiro et al [5] and Fung and Yih [7] scrutinized the peristaltic flows with some hypotheses, such as long wavelength approximation, low Reynolds number, and small amplitude ratio. e problem of peristaltic flow in a tube of Rabinowitsch fluid was scrutinized by Singh and Singh [8]. Singh [9] examined the exact solution of Rabinowitsch peristaltic flow in a tube, and found that the pseudoplastic and dilatant fluids counted on the instantaneous flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Over the most recent couple of years, some researchers have explored peristaltic transport for the Rabinowitsch fluid model. Singh and Singh (2014) investigated peristaltic flow in a tube using Rabinowitsch fluid model. Akbar and Nadeem (2014) studied Rabinowitsch fluid model in peristalsis.…”
Section: Introductionmentioning
confidence: 99%
“…The above model fluid model converts into a pseudoplastic fluid model for (γ>0), Newtonian fluid model when (γ=0), and Dilatant fluid model when (γ<0). The Rabinowitsch model has been confirmed by the investigational results that are obtained by Wada et al 35 Singh et al 36–38 investigated the non‐Newtonian Rabinowitsch fluid model for velocity and pressure gradient relation. Akbar et al 39 discussed the mechanical properties and thermal conductivity effect for the Rabinowitsch fluid model.…”
Section: Introductionmentioning
confidence: 70%